2010
DOI: 10.1063/1.3479529
|View full text |Cite
|
Sign up to set email alerts
|

Strong critical current density enhancement in NiCu/NbN superconducting nanostripes for optical detection

Abstract: We present measurements of ferromagnet/superconductor _NiCu/NbN_ and plain superconducting _NbN_ nanostripes with the linewidth ranging from 150 to 300 nm. The NiCu _3 nm_/NbN _8 nm_bilayers, as compared to NbN _8 nm_, showed a up to six times increase in their critical current density, reaching at 4.2 K the values of 5.5 MAcm2 for a 150 nm wide nanostripe meander and 12.1 MAcm2 for a 300 nm one. We also observed six-time sensitivity enhancement when the 150 nm wide NiCu/NbN nanostripe was used as an optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…2b, we demonstrate that for our best, 18 nm thick NbN lm, J C reaches 8 MA/cm 2 at T = 4.8 K, which is one of the highest values reported in literature, as, typically, I b tends to be reduced by lithography process of the stripe patterning and some substrate atness imperfections [10,11]. We also note that even at T = 14.5 K, J C ≈ 0.2 MA/cm 2 .…”
mentioning
confidence: 56%
“…2b, we demonstrate that for our best, 18 nm thick NbN lm, J C reaches 8 MA/cm 2 at T = 4.8 K, which is one of the highest values reported in literature, as, typically, I b tends to be reduced by lithography process of the stripe patterning and some substrate atness imperfections [10,11]. We also note that even at T = 14.5 K, J C ≈ 0.2 MA/cm 2 .…”
mentioning
confidence: 56%
“…Details of samples' fabrication are reported elsewhere. 21,39 The sputtered samples have been subsequently patterned by electron beam lithography into a meander-type structure consisting of six serially connected blocks, each containing three parallel wires. The elemental wires have width w = 300 nm and length L = 20 μm.…”
Section: Samples and Experimental Methodsmentioning
confidence: 99%
“…20 Lately, the interest in these systems has moved also to nonequilibrium superconductivity. In this field, NbN/CuNi nanostripes showed an increase of the photoresponse amplitude with respect to pure NbN, 21 while Nb/CuNi microbridges presented a reduced slow bolometric contribution compared to the photoresponse of a pure Nb film. 22,23 Moreover, it has been shown that quasiparticle relaxation processes for dirty superconductors, 24 originally calculated as well as experimentally measured with different techniques, are significantly modified in S/F heterostructures.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, it was experimentally proved that S/F hybrids are optimal systems to be used as ultrafast superconducting optical detectors and eventually even as single photon detectors, due to the small value of the penetration length of the superconducting correlations in the F layer, ξ F 6 nm, which determines better performance in terms of both photoresponse signal detection and sensitivity [3][4][5]. In fact, in these devices the light probes a distance α (the material optical penetration depth), which is typically smaller than 50 nm in the 400-900 nm visible light wavelength range [3,4].…”
Section: Introductionmentioning
confidence: 99%